Community mobility reports predict the national spread of COVID-19 in Indonesia in the new normal era - Muhammad Syahrul Ramadhan; Rizma Adlia Syakurah (International Journal of Public Health Science (IJPHS), 2021)
Indonesia government encouraging to new normal life with obeys the health protocol. In Malaysia, the new normal had a significant impact on mobility trends. This study aimed to analyze the community mobility trend (including six categories) and coronavirus disease (COVID-19) daily cases in Indonesia in new normal era. An observational analytic using cross-sectional design. The community mobility data, include mobility trends for six different location categories, were obtained from Google COVID-19 Community Mobility Reports from May 15-July 14, 2020. The Indonesian’s COVID-19 daily cases data were taken from (http://covid19.go.id//) from May 15-July 17, 2020. Time-lag correlation to analyzed community mobility of each location category and COVID-19 daily cases in Indonesia using Pearson Correlation with significance ≤0.05. Recreation, parks, and transit stations have positively strong to very strong, while the residential has negatively strong, and the grocery and pharmacy and workplaces were positively weak to moderate correlations. The community mobility was significantly correlated with the COVID-19 transmission in Indonesia during new normal era, especially in transit stations, retail and recreation. Indonesia government is expected to improve their effort to manage the COVID-19 transmission and consider new policy to curb the COVID-19 transmission.